Diversification of Ironwood Waste as Educational Dental Keychains - Ika Kusuma Wardani; Deby Kania Tri Putri; Erika Norfitriah (Universitas Malahayati Lampung, 2022)
ABSTRACT The incidence of oral disease is primarily due to neglected dental and oral hygiene factors. The leading cause of oral hygiene problems is the lack of knowledge about dental and oral maintenance, so the behavior applied is inappropriate and tends to ignore oral hygiene. This program aims to create media for dental and oral health counseling and increase sales. The method used is counseling, training, mentoring, and evaluation. This program resulted in diversified ironwood waste products and promotions to convey dental and oral health messages. Diversification of ironwood waste into educational dental keychains is expected to improve the level of dental and oral health of the community, especially in South Kalimantan, and is expected to increase sales. Keywords: Diversification, Ironwood Waste, Educational Dental Keychains